Plasmon-Enhanced Multi-Ionization of Small Metal Clusters in Strong Femtosecond Laser Fields - Köller, Lars; Schumacher, M.; Köhn, J.; Teuber, S.; Tiggesbäumker, J.; Meiwes-Broer, Karl-Heinz (Physical Review Letters)
The multiply charging process of platinum cluster ions under intense field conditions show a strong dependence on the width of the femtosecond laser pulse. Increasing the pulse width from 140 to 600 fs while keeping the energy per pulse constant leads to an increase in the highest observed charge state z∗ of the ejected atoms from z∗=13 to z∗=20. This increased charging efficiency is explained by the evolution of the plasmon energy of the metal cluster upon the change in electron density during the Coulomb explosion process. Thus the time dependence of the charging of a cluster in an intense light field has been observed in real time.